Legal Protection for Creditor under Cross Default and Cross Collateral Clause in a Credit Agreement - Sriwati (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
The business developments initiated by businessmen often require large amounts of financing, hence a third party interference is needed. For this purpose, businessmen generally apply for loans or credits from financial institutions, including banks. The legal relationship between a businessman as a debtor and a bank as a creditor is stated in a credit agreement. An issue arises when there is only one creditor with more than one debtor upon one single credit agreement. In such condition, cross default and cross collateral clauses are known. This research will discuss whether the cross default and cross collateral clauses can provide legal protection for a creditor in its credit agreement with the debtors. In conclusion, cross default and cross collateral clauses are not the only factors that provide legal protection for a credit agreement between one creditor and more than one debtors. The guarantee value in the guarantee agreement made must also be adjusted to the total debt value of all related debtors.